ASSESSING DIGITAL KNOWLEDGE AND USAGE AMONG RURAL WOMEN ENTREPRENEURS - Roseliza Hamid; Nik Sarina Nik Md Salleh; Noorazzila Shamsuddin; Khadijah Abdul Rahman; Siti Nur Zahirah Omar (International Journal of Accounting, Finance and Business, 2024)
This study explores the intricate connection between women's entrepreneurship and their proficiency in digital literacy, aiming to grasp the usage patterns among participants. The research focuses on individuals enrolled in the Program Inkubator Usahawan Komuniti Jeli, administered by Pusat Pembangunan Komuniti dan Usahawan (PPKU) UiTM Cawangan Kelantan. These participants, predominantly rural women entrepreneurs, predominantly engage in micro-trading and home-based businesses, notably in the food and beverage and tailoring sectors. Data collection involved disseminating questionnaires among program participants, subsequently analyzed descriptively. The findings indicate that most respondents possess a basic understanding of the internet, exhibiting moderate levels of digital literacy. They typically access the internet through smartphones and tablets, frequently utilizing platforms like Facebook and WhatsApp for browsing. Consequently, the study advocates for tailored digital training initiatives to bolster these entrepreneurs' internet utilization skills for business purposes.